A Suppressor of fab1 Challenges Hypotheses on the Role of Thylakoid Unsaturation in Photosynthetic Function - Barkan, Lenore (American Society of Plant Biologists, 2006)
Leaf membrane lipids of the Arabidopsis (Arabidopsis thaliana) fatty acid biosynthesis 1 (fab1) mutant contain a 35% to 40% increase in the predominant saturated fatty acid 16:0, relative to wild type. This increase in membrane saturation is associated with loss of photosynthetic function and death of mutant plants at low temperatures. We have initiated a suppressor screen for mutations that allow survival of fab1 plants at 2°C. Five suppressor mutants identified in this screen all rescued the collapse of photosynthetic function observed in fab1 plants. While fab1 plants died after 5 to 7 weeks at 2°C, the suppressors remained viable after 16 weeks in the cold, as judged by their ability to resume growth following a return to 22°C and to subsequently produce viable seed. Three of the suppressors had changes in leaf fatty acid composition when compared to fab1, indicating that one mechanism of suppression may involve compensating changes in thylakoid lipid composition. Surprisingly, the suppressor phenotype in one line, S31, was associated with a further substantial increase in lipid saturation. The overall leaf fatty acid composition of S31 plants contained 31% 16:0 compared with 23% in fab1 and 17% in wild type. Biochemical and genetic analysis showed that S31 plants contain a new allele of fatty acid desaturation 5 (fad5), fad5-2, and are therefore partially deficient in activity of the chloroplast 16:0 Δ7 desaturase. A double mutant produced by crossing fab1 to the original fad5-1 allele also remained alive at 2°C, indicating that the fad5-2 mutation is the suppressor in the S31 (fab1 fad5-2) line. Based on the biophysical characteristics of saturated and unsaturated fatty acids, the increased 16:0 in fab1 fad5-2 plants would be expected to exacerbate, rather than ameliorate, low-temperature damage. We propose instead that a change in shape of the major thylakoid lipid, monogalactosyldiacylglycerol, mediated by the fad5-2 mutation, may compensate for changes in lipid structure resulting from the original fab1 mutation. Our identification of mutants that suppress the low-temperature phenotype of fab1 provides new tools to understand the relationship between thylakoid lipid structure and photosynthetic function.